Draw rate management system using mathematical programming in extraction sequence optimisation of block cave mining. (2018) - Nezhadshahmohammad, Farshad; Aghababaei, Hamid; Pourrahimian, Yashar
Planning of caving operations poses complexities in different areas such as safety, ground control and production scheduling. Draw control is fundamental to the success of block-cave operation. Although some complex theories and mathematical draw control systems have been applied in block-cave mines, most of them did not have an exact production rate curve (PRC) to manage draw rates of drawpoints and are too complex to provide a solution for real block-caving mines. This paper presents a mixed-integer linear programming (MILP) model to optimise the extraction sequence of drawpoints over multiple time horizons of block-cave mines with respect to the draw control systems. Four draw rate strategies are formulated to guarantee practical solutions. Furthermore, dilution and caving are improved indirectly, because the method considers the draw rate strategy. Application and comparison of the four models for production scheduling based on draw control systems are presented using 298 drawpoints over 15 periods.